The True Face of Sir Isaac Brock - St-Denis, Guy (University of Calgary Press, 2018)
Major General Sir Isaac Brock is remembered as the Hero of Upper Canada for his defence of what is now Ontario during the War of 1812, and also for his noble death at the Battle of Queenston Heights. In the more than two centuries since then, Brock's likeness has been lost in a confusing array of portraits-most of which are misidentified or conceptual. The 1824 monument constructed to honour Brock's sacrifice was destroyed in 1840 by Benjamin Lett, a disgruntled disciple of William Lyon Mackenzie and critic of the Upper Canadian elite. The replacement and subsequent commemorations emphasized a patriotic desire to visualize the hero's appearance. But despite uncovering an authentic portrait painted only a few years before Brock's death, a series of false faces were promoted to serve competing claims and agendas. St-Denis situates Brock's portraits within an emerging English Canadian imperial nationalism that sought a heroic past which reflected their own aspirations and ambitions. A work of detailed scholarship and a fascinating detective story, The True Face of Sir Isaac Brock details the sometimes petty world of self-proclaimed guardians of the past, the complex process of identification and misidentification that often occurs even at esteemed Canadian institutions, and St-Denis' own meticulous work as he separates fact from fiction to finally reveal Brock's true face.